Hubungan Literasi Sains dengan Kemampuan Clinical Decision Making Mahasiswa Keperawatan - Baiq Fina Farlina (STIKes Hamzar, 2026)
Clinical decision making ability is one of the important competencies that nursing students must possess in providing appropriate and safe nursing care. One of the factors influencing this ability is scientific literacy. Scientific literacy helps students understand scientific concepts, interpret health data, and make decisions based on scientific evidence. This study aimed to determine the relationship between scientific literacy and clinical decision making ability among nursing students at STIKes Hamzar. This research used a quantitative method with a cross sectional design. The sample consisted of 150 respondents selected using proportionate stratified random sampling technique. Research instruments used scientific literacy questionnaires and clinical decision making questionnaires. Data were analyzed using the Spearman Rank test. The results showed that most respondents had good scientific literacy levels (62.7%) and high clinical decision making ability (58.7%). Spearman Rank test showed p-value = 0.001 (<0.05) with correlation coefficient r = 0.682, indicating that the alternative hypothesis was accepted. The conclusion of this study showed a significant relationship between scientific literacy and clinical decision making ability among nursing students at STIKes Hamzar.